Analisis Peran Blantik pada Sistem Pemasaran Domba di Pasar Hewan Tanjungsari - Febiani, Mutia; Daud, Andre Rivianda; Firmansyah, Cecep (Universitas Galuh, 2025)
Tanjungsari Animal Market plays an important role in livestock marketing, especially sheep. The existence of blantik as the main actor mediating transactions between farmers and buyers creates uniqueness in the market. This study aims to analyze the activities of blantik, market actors' perceptions of blantik, and the impact of their presence on the proportion of sheep sales in Tanjungsari Animal Market. The research sample was taken from market players including farmers, traders, blantik, and consumers. Data were obtained through a survey of market participants and analyzed using the Mann-Whitney U Test statistical test. The results showed that there was a significant difference in the proportion of sales between transactions that used blantik and those that did not (p-value = 0.023). The average ranking of transactions with blantik was higher than transactions without blantik, indicating that the role of blantik contributed to improving the smoothness and efficiency of the sheep trade. The presence of blantik helps speed up transactions, expand market access, and improve price stability. However, there are different perceptions among market players regarding the impact of blantik on farmer welfare and supply chain efficiency. This study provides insights into optimizing the role of blantik in the livestock marketing system to improve farmer welfare without compromising consumer interests.